Дані нумізматики про торгівельні шляхи в Україні в середині XІV ст. - Козубовський, Г.А. (Археологія, 2012)
Найважливішими чинниками розвитку торгівельних шляхів у Правобережній Україні XІV ст. визнаються поклади солі та монетарне срібло. Статья посвящена проблеме торговых и экономических связей между западно-украинскими землями (Галиция, Подолия) и золотоордынскими центрами Украины. Анализируется вопрос о существовании торговых путей в Побужье в середине XІV в. Изучение находок медных золотоордынских монет 40—60х гг. XІV в. и пражских грошей показывает, что важнейшие торговые пути существовали, прежде всего, между городами Галиции и Подолии и золотоордынскими центрами в бассейнах Днестра и Буга. Главными стимулами для развития этих торговых путей служили месторождения соли и монетарное серебро. Находки пражских грошей Вацлава II (1300—1305), Яна I Люксембургского (1310—1346) и Карла IV (1346—1378) обозначают важнейшие центры на торговых путях в середине XІV в. Согласно археологическим и нумизматическим данным в середине XІV в. таким значительным пунктом была Торговица на Синюхе. The article is devoted to the problems of trade and economic relations between Western Ukraine lands (Galicia and Podolia) and the Golden Horde centres in Ukraine. An issue of trade routs existence in the Buh River region in the middle of the 14th c. is analyzed. Study of copper Golden Horde coins of the 1340—1350s and Prague groschen shows that the most important trade routs functioned first of all between Galician and Podolian cities and the Golden Horde centres in the Dnister and Buh Rivers basins. Major stimuli for these trade routs development were salt mines and monetary silver. The finds of the Prague groschen of Wenceslaus II (1300—1305), John I Count of Luxembourg (1310—1346) and Charles IV (1346—1378) mark the most important centres on the trade routs in the middle of the 14th c. According to the archaeological and numismatic data, Torhovytsia on the Siniukha River was such important centre in the middle of the 14th c.